Studi Walkability Jalur Pejalan Kaki Rute Kampus Universitas Udayana di Jalan P.B. Sudirman Denpasar - Sidharta, Louis; Kohdrata, Naniek; Dharmadiatmika, I Made Agus (Nandur; Vol 3 No 4 (2023), 2023)
Walking is an important capital for the sustainability of a city. There is already a pedestrian path in the Udayana University Campus area on Panglima Besar Sudirman Street, Denpasar City, but its walkability is not yet known. The research is divided into two pedestrian paths, determined by taking a 400 meter radius from the campus as the location for activity center. Quantitative research methods with observation techniques, surveys and literature studies. The survey used a closed questionnaire instrument with a Likert Scale assessment. This study aims to identify potentials, problems and recommend ideal walkability on the pedestrian path of the research route. Based on the research findings, it can be recommended the use of consistent road materials and widths to increase the walkability of pedestrian paths. Pedestrian path in the Udayana University Campus area on Panglima Besar Sudirman Street already has pedestrian facilities that can support walkability . Supporting facilities can be improved from the parameters of signs and markings, tree shade cover, lighting and trash bins. The ideal walkability on the research route is that it has an average score of Global Walkability Index with a positive trend and is supported by the fulfillment of aspects of accessibility and circulation, width and material consistency and pedestrian path facilities.